Effect of Product Brand Trust on Customer Loyalty - Revi Sesario; Pandu Adi Cakranegara; Gusti Noorlitaria Achmad; Nansi Rianindita; Dedik Wiryawan (Budapest International Research and Critics University, 2022)
The growing world of property in Indonesia has contributed to the growing size of the existing plastic putty industry and the emergence of a new industry in plastic putty. Plastic putty in addition to having a function as an aesthetic. Industrial development in Indonesia is increasing. The government has implemented development in all fields, both physical and non-physical. One form of development is industrial development in Indonesia. The purpose of this study is to analyze effect of product brand trust on customer loyalty. This research uses quantitative research. The sampling technique used is saturated sampling. The population who is also part of the sample in the study are 90 respondents at CV Usaha Jaya Binjai. The type of data used in this research is quantitative. Data analysis used partial test (t). The results show that product brand trust has a positive and unsignificant effect on customer loyalty at CV Usaha Jaya Binjai. There are recommendations that can be used as suggestions for companies to pay more attention to brand loyalty and trust in customers so that customers can feel satisfied with the products they produce. Companies must take promotional actions and expand marketing techniques so that market segmentation of the brands sold.